FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ISPA PADA ANAK BALITA DI KOTA MAKASSAR - Zaenal (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2020)
Acute Respiratory tract infections (RESPIRATORY) is one of the leading causes of death in children in developing countries. This research aims to know the relationship of maternal education, home ventilation, the use of the anti mosquitos, the presence of smokers with RESPIRATORY events in toddlers with this type of research is observational, approach Cross Sectional Study. This research will be done in Barombong village Sub district Tamalate Makassar city and will be implemented in May-June of 2013. The population in this research is all the toddlers there i.e. 1291 toddlers. Sample research by using Simple Random Sampling. Data collection is done using primary data and secondary data. Statistical analysis the results obtained the present education namely amounting to 5,579% (p = 0,018), ventilating the House of 8,002% (p = 0,005), using the anti mosquitos burn of 8,306 (p = 0.004), the presence of smokers 5,779 (p = 0.016)